1996
DOI: 10.1128/jvi.70.8.5115-5122.1996
|View full text |Cite
|
Sign up to set email alerts
|

A single gene encoding the fiber is responsible for variations in virulence in the fowl adenoviruses

Abstract: Intertypic recombinant fowl adenoviruses (FAVs) were generated to determine regions of the viral genome involved in virulence. Recombinants were produced with two serotype 8 FAVs, mildly virulent CFA 3 and hypervirulent CFA 40. Restriction endonuclease fragments from the genomes of the two FAVs were used to transfect primary chicken kidney cells. Virulence testing of these recombinants located the region responsible for differences in virulence to an 8.4-kb fragment of the genome located between kb 26.6 and 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…With regard to the virulence association of fibre-2, previous studies reported that this protein has an effect on the virulence of fowl adenovirus (Pallister et al, 1996). Additionally, aligning fibre-2 amino acid sequences of several FAdVs-4 which induce HHS and apathogenic strains, we noted particular amino acid substitutions between both kinds of strains (Marek et al, 2012).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…With regard to the virulence association of fibre-2, previous studies reported that this protein has an effect on the virulence of fowl adenovirus (Pallister et al, 1996). Additionally, aligning fibre-2 amino acid sequences of several FAdVs-4 which induce HHS and apathogenic strains, we noted particular amino acid substitutions between both kinds of strains (Marek et al, 2012).…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown the important role of fibre-2 in virulence of fowl aviadenoviruses (Pallister et al, 1996). Some authors suggested some amino acids relevant for virulence based on the amino acid comparison of strains which induce HHS and non-virulent strains, positions located at 219 and 380 in the fibre-2 protein of KR5 (Marek et al, 2012).…”
Section: Fibre Proteinsmentioning
confidence: 99%
“…Finally, the purification of the virus by ultracentrifugation in a caesium-chloride gradient in earlier studies resulted in a virus stock that had lost its ability to haemagglutinate, even though its infectivity in tissue culture and eggs remained unaltered. The tissue tropism of adenoviruses is primarily determined by epitopes on the fibre protein, the haemagglutinin (Pallister et al, 1996). It is likely, therefore, that changes in the haemagglutination properties might influence pathogenicity, even if in vitro infectivity is retained.…”
Section: Discussionmentioning
confidence: 99%
“…Among the structural proteins encoded by adenovirus, the fiber protein plays vital roles in mediating viral infection and determining the antigenicity [ 17 19 ]. In contrast to other adenoviruses, FAdV-1, FAdV-4 and FAdV-10 encode two fiber proteins, designated fiber-1 and fiber-2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%